A treasury of pet stories - Carnell, Suzanne; Reid, Mick (New York : Kingfisher, 1997)
"A collection of seventeen stories featuring a wide range of pets, by such authors as Ted Hughes, Beverly Cleary, and Margaret Mahy."
Keywords: Pets -- Juvenile fiction; Children's stories; Pets -- Fiction; Short stories